Dynamic Single-Photon Emission Computed Tomography Data Analysis: Capabilities for Determining Functional Significance of Coronary Artery Atherosclerosis; MATEC Web of Conferences; Vol. 79 : Information-Measuring Equipment and Technologies (IME&T 2016) - Mochula A. Andrew; Zavadovsky K. V. Konstantin Valerievich; Andreev S. Sergey; Lishmanov Yu. B. Yury Borisovich (2016, 2016)
Title screen